Dendrimer-coated carbon nanotubes deliver dsRNA and increase the efficacy of gene knockdown in the red flour beetle Tribolium castaneum - Catriona H. Edwards (Nature Portfolio, 2020)
Abstract In this study, the use of dendrimer-coated carbon nanotubes (CNTs) as a delivery vehicle for dsRNA was assessed in Tribolium castaneum. Exposure to low dosages of polyamidoamine dendrimer carbon nanotubes (PAMAM-CNTs) did not affect T. castaneum larval mortality. Expression of key apoptotic factors, Dronc (Tc12580), Dredd (Tcn-like, Tc014026) and Buffy, (Tcinhib apop1), which can act as toxicity indicators, were not altered in T. castaneum larvae following injection of PAMAM-CNTs. The level of knockdown of two target genes, α-tubulin and mitochondrial RNA polymerase (mtpol), were significantly increased when larvae were injected with double-stranded RNA bound to CNTs (PAMAM-CNT-dsRNA), compared to those injected with target dsRNA alone. PAMAM-CNTs were visualised in cellular vacuoles and in the cell nucleus. Increase occurrence of a blistered wing phenotype was found in a subset of PAMAM-CNT-dsRNAαtub injected larvae, relative to the level seen in larvae injected with naked dsRNAαtub alone. These results suggest that the use of functionalised CNTs for dsRNA delivery could increase the efficacy of RNA interference in insect pest species.